Heterogeneous Islam as a Cultural Identity of Multicultural Communities in the Suburbs of Pontianak - Yusriadi, Yusriadi; Muttaqin, Imron (Al-Albab, 2018)
This article discusses the variant of Islam that lives in a multicultural society in the Sungai Ambawang area in the suburbs of Pontianak City, West Kalimantan. In the Javanese, Bugis, Malay and Madurese communities, Islam has served as an important element in the formation of their cultural identity, thus causing them to be synonymous with the Islamic community. Islamic elements that are used and have become part of the culture of society include the choice of Islamic dates such as the Hijri month in determining the time of cultural activities, the use of Al-fitihah and several other verses from the Qur’an as well as shalawat and prayer, the use of mosques as a center of cultural activities and the involvement of Islamic religious leaders in traditional ceremonies. The use of these elements has become a hallmark of the community culture and its form has been preserved until today.